2018
DOI: 10.1038/s41598-018-33019-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Differences in Metabolic Activity of Melanoma Models on Response to Lonidamine plus Doxorubicin

Abstract: Lonidamine (LND), a metabolic modulator, sensitizes DB-1 human melanoma to doxorubicin (DOX) chemotherapy by acidifying and de-energizing the tumor. This report compares the effects of LND on two human melanoma lines, DB-1 and WM983B, which exhibit different metabolic properties. Using liquid chromatography mass spectrometry and Seahorse analysis, we show that DB-1 was more glycolytic than WM983B in vitro. 31P magnetic resonance spectroscopy (MRS) indicates that LND (100 mg/kg, i.p.) induces similar selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Thus, the pH gradient of tumor was reversed so that free basic DOX (pKa ~8.5) would be more readily captured in the acidified tumor cells (cation trapping) [ 54 ]; (2) for another, similar to TMZ and NM, LND-mediated tumor de-energization inhibits energy-dependent MDR efflux pumps, resulting in more DOX retained in tumor cells. In 2018, Nath et al reported the combined effect of LND plus DOX against two different human melanoma cell lines (DB-1 and WM983B) [ 56 ]. It was found that WM983B melanoma was less glycolytic than DB-1, however, intracellular acidification and de-energization were also induced after exposure to LND in immunosuppressed mice WM983B xenografts.…”
Section: Combination Of Lnd With Chemotherapeutic Drugsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the pH gradient of tumor was reversed so that free basic DOX (pKa ~8.5) would be more readily captured in the acidified tumor cells (cation trapping) [ 54 ]; (2) for another, similar to TMZ and NM, LND-mediated tumor de-energization inhibits energy-dependent MDR efflux pumps, resulting in more DOX retained in tumor cells. In 2018, Nath et al reported the combined effect of LND plus DOX against two different human melanoma cell lines (DB-1 and WM983B) [ 56 ]. It was found that WM983B melanoma was less glycolytic than DB-1, however, intracellular acidification and de-energization were also induced after exposure to LND in immunosuppressed mice WM983B xenografts.…”
Section: Combination Of Lnd With Chemotherapeutic Drugsmentioning
confidence: 99%
“…In addition to enhanced glycolysis, the increased pentose phosphate pathway (PPP) flux, the high rates of glutaminolysis, and the synthesis of fatty acids (FAs) are also the malignant metabolic phenotypes of cancer cells [ 58 , 84 , 85 ]. When glycolysis is inhibited, glucose metabolism is impaired; however, tumor cells can survive by utilizing the glutaminolysis as a complementary surviving pathway, and vice versa [ 56 , 58 ]. Therefore, it is considered to kill cancer cells through the combined inhibition of malignant metabolic pathways.…”
Section: Combination Of Lnd With Chemotherapeutic Drugsmentioning
confidence: 99%
See 3 more Smart Citations